Correspondencia entre Enrique S. Mestre, Victoriano Fernández y Roberto H. Todd - Mestre, Enrique S.; Fernández, Victoriano; Todd, Roberto H. (My University, 1935)
Donativos a favor de la viuda e hijos de Manuel A. Martínez Dávila.
Keywords: Martínez Dávila, Manuel A.,1883-1934; Porrata Doria, Adolfo; Díaz, Elias; Fernández, Victoriano M.